Safeguarding Young Lives: The Critical Role of Government in Addressing Sexual Violence Against Children in Indonesia - Samuel, Maria Gabriela; Yolanda, Maureen Keisha; Gunadi, Ariawan (Journal of Health Education Law Information and Humanities, 2025)
Sexual violence against children is an urgent issue that has become a global concern, including in Indonesia. Although the Indonesian government has issued various policies and regulations to address this issue, implementing the policies and regulations still faces significant obstacles. These include the establishment of a Regional Technical Service Unit for the Protection of Women and Children (UPTD PPA), training programs for relevant institutions, and educational campaigns for the prevention of sexual violence against children. However, the prevalence of sexual violence against children remains alarmingly high, with over 11,000 cases reported in 2022. The main factors contributing to the high rate of child sexual abuse are weak law enforcement, lack of coordination between institutions, and cultural barriers that hinder understanding and education about child protection. Additionally, resistance to implementing the Child Protection Law highlights the gap between policy formulation and practical law enforcement. In order to minimize the incidence of sexual violence against children, this study emphasizes the necessity of greater collaboration among the society, non-governmental organizations (NGOs), the private sector, and the government. The research further highlights the need to raise awareness of the significance of children's rights and sexual violence prevention. Key recommendations include strengthening the implementation of the policies and regulations, improving law enforcement, and enhancing the capacity of law enforcement institutions in order for child protection policies to be implemented more effectively and efficiently.